Myelopathy but normal MRI: where next?. Issue 2 (14th March 2008) - Wong, S H; Boggild, M; Enevoldson, T P; Fletcher, N A
Abstract : For most patients presenting with a spinal cord syndrome MR scanning has become the key investigation in establishing the diagnosis. However, myelopathy with normal spinal imaging remains a common clinical conundrum. In this review we discuss the diagnoses to consider for the neurologist presented with a patient with "MR normal myelopathy". We will illustrate this scenario with a series of short cases and consider the further investigation of "MRI normal" myelopathy.